Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2016)
We report, for the first time, the remarkable efficacy of uttroside B, a potent saponin from Solanum nigrum Linn, against liver cancer. The compound has been isolated and characterized from the leaves of Solanum nigrum Linn, a plant widely used in traditional medicine and is a rich resource of several anticancer molecules. Uttroside B, that comprises of beta-D-glucopyranosyl unit at C-26 of the furostanol and beta-lycotetraosyl unit at C-3, is ten times more cytotoxic to the liver cancer cell line, HepG2 (IC50: 0.5 mu M) than sorafenib (IC50: 5.8 mu M), the only FDA-approved drug for liver cancer. Moreover, it induces cytotoxicity in all liver cancer cell lines, irrespective of their HBV status, while being non-toxic to normal immortalized hepatocytes. It induces apoptosis in HepG2 cells by down-regulating mainly the activation of MAPK and mTOR pathways. The drastic reduction in HepG2-xenograft tumor size achieved by uttroside B in NOD-SCID mice and substantiation of its biological safety through both acute and chronic toxicity studies in Swiss albino mice warrants clinical validation of the molecule against hepatic cancer, for which, the chemotherapeutic armamentarium currently has limited weapons.

Evaluation of uttroside B, a saponin from Solanum nigrum Linn, as a promising chemotherapeutic agent against hepatocellular carcinoma (vol 6, 36318, 2016) - Nath, Lekshmi R.; Gorantla, Jaggaiah N.; Thulasidasan, Arun Kumar T.; Vijayakurup, Vinod; Shah, Shabna; Anwer, Shabna; Joseph, Sophia M.; Antony, Jayesh; Veena, Kollery Suresh; Sundaram, Sankar; Marelli, Udaya K.; Lankalapalli, Ravi S.; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.